2019
DOI: 10.1111/imj.14192
|View full text |Cite
|
Sign up to set email alerts
|

Assessment, incidence and factors associated with urinary incontinence in older Aboriginal Australians

Abstract: Background:Little is known about urinary incontinence in older Aboriginal Australians.Aim: To describe urinary incontinence assessment, prevalence, incidence and associated conditions in older Aboriginal Australians.Methods: Wave 1 consisted of 363 Aboriginal participants aged ≥45 years from Western Australia; 289 participants participated in Wave 2, with 184 included at both time points. Urinary incontinence was assessed by self-report, family report and the modified International Consultation on Incontinence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
(25 reference statements)
2
7
0
Order By: Relevance
“…Age is an established risk factor for SUI and UUI 4,10,27 . Our findings further confirmed that the risk of SUI and UUI increased with age in the general population.…”
Section: Discussionsupporting
confidence: 87%
“…Age is an established risk factor for SUI and UUI 4,10,27 . Our findings further confirmed that the risk of SUI and UUI increased with age in the general population.…”
Section: Discussionsupporting
confidence: 87%
“…After screening the titles and abstracts, 19 articles fulfilled the inclusion criteria. Full‐text screening identified only 11 papers dealing with the subject of the review 7,8,14‐22 . See Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Smith and colleagues 14 made an effort to describe the issue of urinary incontinence in the older Australian Aboriginal population. They conducted a cross‐sectional study at two time periods—first in 2004–2006 and then again in 2011–2013—both in remote Kimberley communities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The annual incidence of UI reportedly ranges from 1% to 11%, and the remission rate of UI ranges from 5% to 11%. 7–12 However, few large-scale studies quantifying the rates of progression and remission in Asia are available. Knowledge of natural changes in UI subtypes, ie stress UI (SUI), urgency UI (UUI) and mixed UI (MUI), is critical to the prevention and development of different clinical management and treatment strategies along the disease continuum.…”
mentioning
confidence: 99%